Ceramah Edukasi Digital Marketing Pada Gki Taman Aries dan GKI Kemang Pratama Bekasi - Selvi Esther Suwu (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2020)
The existence of a pandemic in 2020 changes the life of people's purchasing behavior, namely those who usually shop at traditional and modern markets because of fear and the government's appeal to continue to carry out all activities from home, switch shopping from home. As a result, many shops and shopping centers have closed and resulted in many people being laid off. Covid19 cannot predict when it will end and people still have to struggle to live, so against this background the aim of PkM GKI Taman Aries and GKI Kemang Pratama is to hold events to meet the needs of congregations and communities who need additional knowledge about general economic subject matter so that can make a business or defend his business with more creative endeavors. Participants came from various regions in Indonesia reaching 448 people at PkM GKI Taman Aries and at GKI Kemang Pratama participants could watch on YouTube because the event was broadcast live. The author as a lecturer responded to this event by speaking about digital marketing as part of PkM. The method of implementing PkM is in the form of educational lectures using the internet media, namely Zoom. The results obtained from the two PkM activities were that the participants thought that educational lectures increased knowledge, that the author's presentations could be understood clearly, the discussion was practical and concise.